2007
DOI: 10.1159/000109623
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of complex rearrangements at translocation breakpoints in a transgenic mouse; implications for mechanisms involved in the formation of chromosome rearrangements

Abstract: Cryptic complex rearrangements as a result of a reciprocal chromosome translocation have been characterised in a transgenic mouse strain. Analysis of the breakpoint junctions in our previous studies showed that the ada transgene was integrated at the breakpoint forming a fusion gene with Golga3 (Mea2). In this study, further detailed analysis around the translocation junctions revealed that the surrounding regions were composed of 13 fragments of defined transgenic chromosome origins over approximately 1.9-Mb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(22 reference statements)
2
3
0
Order By: Relevance
“…The transgene copy fusions identified in this study are consistent with complex rearrangements of gene concatemers observed in other transgenic mice (2932). The fusions could have arisen independently of each other, by either non-homologous end-joining or recombination, as suggested for modifications observed in other types of transgenes after their integration (33,34), or in the case of R2, by sequence degradation due to nuclease ‘nibbling’ (30,35,36).…”
Section: Resultssupporting
confidence: 88%
“…The transgene copy fusions identified in this study are consistent with complex rearrangements of gene concatemers observed in other transgenic mice (2932). The fusions could have arisen independently of each other, by either non-homologous end-joining or recombination, as suggested for modifications observed in other types of transgenes after their integration (33,34), or in the case of R2, by sequence degradation due to nuclease ‘nibbling’ (30,35,36).…”
Section: Resultssupporting
confidence: 88%
“…Transgene integration sites were detected at the border of 1R and 6A chromosomes translocations in line hybrid-A. This is in agreement with the observations that transgene insertion sites are frequently associated with chromosomal rearrangements (Chiang et al 2012;Le Saux et al 2010;Kasai et al 2007). Previous studies indicated that translocation breakpoints were often located at the border of C-bands and the euchromatin region or between two adjacent C-bands in wheat (Taketa and Kawahara 1996;Badaeva et al 2007).…”
Section: Transgenic Ressupporting
confidence: 90%
“…Reported rearrangements include deletions, duplications, inversions and translocations (7–9,13,14) reviewed earlier by Wrutele et al (15). These integrations and rearrangements of genomic structure are of particular interest to the fields of cancer and gene therapy.…”
Section: Resultsmentioning
confidence: 99%